The Struggles of Identity, Education, and Agency in the Lives of Undocumented Students The Burden of Hyperdocumentation - Chang, Aurora (Springer International Publishing, 2018)
This book weaves together two distinct and powerfully related sources of knowledge: the author's journey and transition from a once undocumented immigrant from Guatemala to a hyperdocumented academic, and five years of on-going national research on the identity, education, and agency of undocumented college students. In interlacing both personal experiences with findings from her empirical qualitative research, Chang explores practical and theoretical pedagogical, curricular, and policy-related discussions around issues that impact undocumented immigrants while provide compelling rich narrative vignettes. Collectively, these findings support the argument that undocumented students can cultivate an empowering self-identity by performing the role of infallible cultural citizen. .